Os limites para instituição de obrigações tributárias acessórias à luz do princípio da proporcionalidade e do dever fundamental de contribuir com os gastos públicos - Tavares, Henrique da Cunha (2014)
The accomplishment of the fundamental duty to contribute to public spending is essential, in tax states like Brazil, for collection the financial resources needed to materialize the fundamental rights. The accessory tax obligations play an important role in the enforcement of this duty. The last ten years have seen, in Brazil , an exponential increase in accessory tax obligations, in a clear intent to transfer, for individuals, the task of state administration, management and supervision of taxes. All ancillary tax liability reaches, a greater or lesser extent, fundamental rights attached to liberty and property of individuals. Motivated by inflation of accessory tax obligations and their impact on fundamental rights of the people, the study sought to identify which are the constitutional limits to the imposition of these obligations. To do so, using the deductive method and literature, some constitutional principles and rules applicable to the tax legal relationship maintained between the state and private were analyzed. Finally, these principles and rules have been weighted by means of the principle of proportionality, with some concrete hypotheses accessory tax obligations . From these considerations, limits that must be observed for the imposition of accessory tax obligations proportionate were extracted. It was concluded that: 1 ) are unconstitutional, accessory tax obligations, as well as the penalties resulting from them, they are useless to achieve the purpose of assisting in the collection and enforcement of taxes; 2) any accessory tax obligation unnecessary is excessively burdensome, and therefore unconstitutional; 3 ) are unconstitutional, accessory tax obligations that the jusfundamental affectation caused by it is disproportionate, in the strict sense, to her profit for the interest of the collection and enforcement of taxes . Bibliographical sources, objectives , hypotheses and research findings reinforce that work has adhesion to search for fundamental rights.